The Influence of Reliability, Responsiveness, and Empathy on Visitor Satisfaction at the Jazz Traffic Festival 2025 - Andini Raissa Putri; Sheidy Yudhiasta (Ann Publisher, 2026)
Introduction. The Jazz Traffic Festival is one of the largest music festivals, attracting many attendees each year. The success of the event depends not only on the quality of the performance, but also on the quality of service which determines the level of visitor happiness. However, the contradictory results of prior studies indicate that further research is needed. Goal. This study intends to investigate the influence of reliability, responsiveness, and empathy on the happiness of visitors to the Jazz Traffic Festival 2025.Methods This research was carried out utilizing a quantitative methodology through a survey with 100 visitors of the Jazz Traffic Festival 2025. Data were analyzed using SPSS software to perform multiple linear regression analysis. Results. The study's findings indicate that, when considered individually, the responsiveness variable significantly and favorably affects visitor satisfaction, while the reliability and empathy variables do not show a significant effect. When considered together, all three variables were determined to have a considerable effect on visitor satisfaction. Conclusions. The responsiveness dimension is the service quality dimension that contributes most to visitor satisfaction at the Jazz Traffic Festival 2025.